EFFECTIVENESS OF MARINE FUNGI AS FEED ADDITIVE ON NATIVE CHICKEN PERFORMANCE - Nurhayati, Nurhayati; Nelwida , Nelwida; Lisna, Lisna; Ramadan , Fauzan; Tarman, Kustiariyah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted to determine the effectiveness of marine fungi as a feed additive on the performance of native chickens. One hundred and eighty unsex one-day-old native chickens were used in this study. Chickens were kept for ten weeks and given a treatment supplemented with the dietary marine fungi (1, 2, 3, and 4 ml/kg) in a ration consisting of yellow corn, rice bran, fish meal, soybean meal, coconut meal, L-lysine, methionine, and CaCO3. The data collected were feed consumption, body weight gain, carcass percentage, mortality rate, and feed efficiency. The results showed significant (P